(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The study examined and discussed the morphology and variability of male genitalia in the Bombinae subfamily, with a comparison of the nomenclature used by former Authors. The characteristics of the considered apparatus have been used to draw up a dichotomic key of the subgenera of Psithyrus Lepeletier s.l. and Bombus Latreille s.l. which can be found in Italy, accompanied by SEM-photos of each subgenus.